Profiles in corruption : abuse of power by America's progressive elite - Schweizer, Peter, 1964- (Harper an imprint of HarperCollins Publishers, 2020)
"Washington insiders operate by a proven credo: when a Peter Schweizer book drops, duck and brace for impact. For over a decade, the work of five-time New York Times bestselling investigative reporter Peter Schweizer has sent shockwaves through the political universe."--Amazon.com